Soldier photography of detainee abuse in Iraq: digital technology, human rights and the death of Baha Mousa - Whitty, Noel (Oxford University Press, 2010)
Digital media technologies provide new opportunities for the recording and publicising of human rights violations. In recent years, soldier photography during military conflicts has become one of the most controversial sources of images of abuse, especially in relation to the visual representation of detainees. The backdrop to this article is the death of Baha Mousa, an Iraqi civilian who died while in detention on a British Army military base in Basra in southern Iraq in 2003. A soldier’s video footage of Mr Mousa’s treatment in the detention facility has helped to generate a range of cultural, political and legal effects, not least an ongoing official Inquiry into the causes of his death. But while new media technologies, such as mobile camera-phones, can provide an expanded visual record of human suffering and death in war zones, this article argues that this brings dangers as well as possibilities. More generally, it raises questions about how human rights practitioners should respond to the increasing visualisation of witnessing.